Hypofractionated Radiotherapy for Palliation of Main Portal Vein Tumor Thrombosis - Fang, Fang; Qiu, Bin; Zhen, Peng; Wang, Junjie (Frontiers in Oncology, 2022)
Background: Hypofractionated radiotherapy delivered for portal vein tumor thrombosis (PVTT) located in the main portal vein is rarely exploited. The study aimed to evaluate the efficacy and safety of hypofractionated radiotherapy as palliative treatment for PVTT in cirrhotic patients with hepatocellular carcinoma. Methods: From March 2016 to July 2020, 16 patients (mean age, 59.1±6.3 years; 15 males) with hepatocellular carcinoma and hepatitis virus-related cirrhosis underwent hypofractionated radiotherapy for PVTT (located in the main portal vein) in our institute were retrospectively reviewed. Results: Complete response of the PVTT was observed in 4 cases (25%) with partial response in 7 cases (43.75%) and stable disease in 5 cases (31.25%). Symptom relief was observed in all 7 patients suffering from ventosity. The median time to progression was 6 months (Interquartile range, IQR: 6–12 months). Eight patients (50%) failed due to primary cancer progression, 7 patients failed due to extrahepatic metastasis, and only 1 patient failed due to PVTT progression. The median overall survival was 17.4 months (IQR: 8–25 months). Grade I/II anorexia/nausea was observed in 14 patients (87.5%) and Grade I/II leukopenia was observed in 14 patients (87.5%). No complications ≥ Grade III was observed. Conclusions: Hypofractionated radiotherapy as palliative treatment appears effective and safe for PVTT located in the main portal vein in cirrhotic patients with advanced hepatocellular carcinoma yielding a high rate of tumor response. Further study is warranted.